Penerapan Teori Golden Section Pada Foto Landscape Pantai Di Gunungkidul - Nofria Doni Fitri; R Hadapiningrani K (AKSA: Jurnal Desain Komunikasi Visual, 2020)
Technical problems in the digital photography era have now beenovercome by the sophistication of cameras. The problem thattechnology cannot solve is the composition of the image.Composition is a skill that requires an understanding ofphotographic objects, visual elements, and artistic experience.Composition is related to the placement of objects and how to build aflow of view in viewing photos that have an impact on the impressionof the photo. The decision to press the camera's shutter button is aconsideration of composition, and is not easily understood bystudents or beginners who are just learning photography. So thatwith knowledge of the composition of this golden section,photographers can produce more optimal work. Careful at everyvisual element that exists, skilled in arranging objects so that bettervisuals are created. Super-sophisticated camera technology cannotsearch for objects on its own, therefore this research is offered. TheGolden Section Theory has been successfully applied to the field ofarchitecture in the 5th century BC and in the field of painting duringthe renessance era. In this study, the author tries to apply thisformula to determine the main object (center of attention) in a beachscene photo in Gunungkidul in 2: 3 image format or the defaultDSLR camera format.